Sodium–Glucose CoTransporter-2 Inhibitor Empagliflozin Ameliorates Sunitinib-Induced Cardiac Dysfunction via Regulation of AMPK–mTOR Signaling Pathway–Mediated Autophagy - Ren, Changzhen; Sun, Kaiqiang; Zhang, Yanda; Hu, Yangxi; Hu, Bowen; Zhao, Jian; He, Zhiqing; Ding, Ru; Wang, Weizhong; Liang, Chun (Frontiers in Pharmacology, 2021)
Background: Sodium-glucose co-transporter 2 (SGLT2) inhibitors have been shown to decrease the adverse cardiac events and risks of cardiovascular mortality among patients with or without diabetes, which has made these drugs promising treatment options for patients with chronic heart failure. Cardiac dysfunction is a common and severe side-effect inducing by cancer chemotherapies, which seriously affects the prognosis and life quality of tumor patients. However, it is not clear whether SGLT2 inhibitors have cardiovascular benefits in patients with cancer chemotherapy-related cardiac dysfunction. We aimed to determine whether empagliflozin (EMPA), an SGLT2 inhibitor, has a protective role against sunitinib (SNT)-induced cardiac dysfunction in a mouse model. Methods: Male C57BL/6J mice were randomized into control (Control, n=8), empagliflozin (EMPA, n=8), sunitinib (SNT, n=12) or sunitinib and empagliflozin co-administration (SNT+EMPA, n=12) groups. EMPA, SNT or SNT combined EMPA was given via oral gavage for consecutive 28 days, respectively. Cardiovascular functions and pathological changes were examined and the underlying mechanisms of EMPA's effects were investigated in H9c2 cardiomyocytes. Results: Mice in SNT group exhibited dramatically elevated blood pressure (systolic blood pressure [SBP] 134.30 ± 6.455 mmHg vs. 114.85 ± 6.30 mmHg), as well as impaired left ventricular function (left ventricular ejection fraction [LVEF] 50.24 ± 3.06 % vs. 84.92 ± 2.02 %), as compared with those of control group. However, EMPA could ameliorate SNT-induced cardiotoxicity, both in terms of SBP (117.51 ± 5.28 mmHg vs. 134.30 ± 6.455 mmHg) and LVEF (76.18 ± 5.16 % vs. 50.24 ± 3.06 %). In H9c2 cardiomyocytes, SNT-induced cardiomyocyte death and cell viability loss as well as dysfunction of adenosine 5′-monophosphate-activated protein kinase-mammalian target of rapamycin (AMPK-mTOR) signaling mediated autophagy were restored by EMPA. However, these favorable effects mediated by EMPA were blocked by inhibition of AMPK or autophagy. Conclusion: EMPA could ameliorate SNT-induced cardiac dysfunction via regulating cardiomyocyte autophagy, which was mediated by AMPK-mTOR signaling pathway. These findings supported that SGLT2 inhibitor therapy could be a potential cardioprotective approach for cardiovascular complications among patients receiving SNT. However, these favorable effects still needs to be validated in clinical trials.